2011
DOI: 10.1021/jp207713x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophilic and Hydrophobic Nanoparticles on the Surface Pressure Response of DPPC Monolayers

Abstract: The study of the interaction between Langmuir monolayers of 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine (DPPC), as the major component of lung surfactant (LS), and nanoparticles of different nature, hydrophilic silica (SiO 2 ) and hydrophobic carbon black (CB), has been carried out by measuring the compression ΠÀA isotherms and the response of the surface pressure to harmonic variations of the interfacial area simulating respiratory cycles in a Langmuir trough. The change of the monolayer interfacial structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
119
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 47 publications
9
119
2
Order By: Relevance
“…Recent studies have focused on the toxicology of SiO 2 NPs and have found that SiO 2 NPs can cause harmful biological responses in diverse organs. [4][5][6][7][8][9] The liver, as the major organ for the biotransformation of toxins, is a primary target organ for nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the toxicology of SiO 2 NPs and have found that SiO 2 NPs can cause harmful biological responses in diverse organs. [4][5][6][7][8][9] The liver, as the major organ for the biotransformation of toxins, is a primary target organ for nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although silica is generally considered to be noncytotoxic, 8 designing silica as nanomaterials may change its biocompatibility because of changes in its physicochemical properties, and its use for biomedical devices should be verified. 7,9,10 A previous study of the biocompatibility of MPS has investigated the general effects of nanomaterials such as size, surface charge, concentration, and morphology. 11 However, the largest expected influence on the difference in biocompatibility between MPS and Col NPs is the pore structure property.…”
Section: Introductionmentioning
confidence: 99%
“…Further understanding of the interaction of NP with the PS have been obtained by the investigation of deposited mixed lipid-NP layers at the aqueous surface. Such surface science approach, utilizing a set of different techniques (Langmuir trough, surface rheology, AFM, Brewster Angle microscopy, ellipsometry), allowed significant effects of the NPs on the structural and dynamic features of model PS to be identified [12,13], such as, modifications of the linearity (see Fig. 1) of its surface tension response under surface area expansion-compression cycles and of the 2-D phase behavior, which are potentially relevant for the impairment of the lung functionality.…”
Section: Interactions Of Inhaled Droplets and Particles With Human Brmentioning
confidence: 99%